Alternative Genetically Modified Organisms, Organics and The Contested Construction of Demand in the Agro-food System - Wilkinson, John (The International Journal of Sociology of Agriculture and Food, 2021)
This article argues that the examples of genetically modified organisms (GMOs) and organics call for a critical reappraisal of demand and consumer theory as applied to agro-food studies. While GMOs have been the object of unprecedented opposition in spite of their unanimous adoption by upstream multinationals, organics have experienced spectacular autonomous growth leading to belated adaptive responses by the major downstream actors. After examining the implications of these two developments, the article discusses the contested dynamics of demand formation in the agro-food system and the different ways in which broader demand trends influence food consumption patterns. It also calls attention to the central role of new civic and State actors in analysing the alliances now emerging within the agro-food system.